Plasma homocysteine, folate and vitamin b12 levels in patients with lung cancer - Taştekin, Didem; Ertürk, Kayhan; Bozbey, Hamza Uğur; Ölmüşçelik, Oktay; Kızıltan, Huriye Şenay; Tuna, Savaş; Taş, Faruk (Morion, 2015)
Aim: Disorders in the metabolism of homocysteine and B vitamins, which are involved in a one-carbon transfer reaction and important for DNA synthesis and methylation, have been hypothesized to be associated with carcinogenesis. The purpose of this study is to evaluate the levels of homocysteine, vitamin B12 and folic acid in patients with newly diagnosed lung cancer and determines whether they might be used as an accurate tumor marker for monitoring the patients if they are found to be elevated in lung cancer. Materials and Methods: Forty male patients with lung cancer were included in this study. Age-matched forty healthy males who had not malignant disease or had not received any drug affecting plasma homocysteine levels were selected as control group. Homocysteine, vitamin B12 and folate levels were measured in the samples obtained from the patients and controls. Results: Mean age of the patients with lung cancer was 58.7 ± 9.9 years. All the patients were cigarettes smokers. Mean daily consumption of cigarettes was 2.0±0.7 packs and mean duration of smoking was 30 ± 11 years. Histologic type of carcinoma was found to be squamous cell carcinoma in 55%, adenocarcinoma - in 35%, and small cell carcinoma - in 10% of the cases. Clinical stage was stage IA in 20%, stage IB - in 20%, stage IIA - in 2.5%, stage IIB - in 10%, stage IIIA - in 12.5%, stage IIIB - in 20%, and stage IV - in 15% of the cases. Mean homocysteine level was 15.3 ± 7.3 µmol/l in the patients with lung cancer while 9.8 ± 2.6 µmol/l in controls. Homocysteine level was significantly higher in the patients with lung cancer compared to control group (p < 0.001). Mean folate level was 4.3 ± 1.8 pg/ml in cancer cases while 6.1 ± 2.3 pg/ml in controls. That is to say, plasma folate levels were significantly lower in cases of lung cancer compared to controls (p < 0.001). There was no significantly difference between groups with regard to B12 levels (mean B12 level was 234 ± 99 and 240 ± 104 ng/ml in the patients with lung cancer and controls, respectively, p = 0.78). Plasma homocysteine, vitamin B12 and folate levels did not show significant difference with respect to histologic type of carcinoma. No significant correlation was found between plasma homocysteine, vitamin B12, folate levels and number of cigarettes smoked per day, duration of smoking, age of the patient, and clinical stage of carcinoma. There was also no correlation between number of cigarettes smoked per day, duration of smoking, age of the patient and clinical stage of carcinoma. A possible inverse correlation between plasma homocysteine, vitamin B12 and folate levels was not observed. Conclusion: In conclusion, high plasma homocysteine and low folate levels could be associated with lung cancer. However, further studies performed on large patient population are needed.
Keywords: Folate; Homocysteine; Lung Cancer; Vitamin B12